What do people look for in a potential partner after the age of 50? - Fernández-Alonso, Mercedes (SAGE, 2023)
The intimate relationships of the older population have seldom been analyzed from a sociological perspective. This study provides novel information on what is desired in a partner after the age of 50 in Spain. The academic debate on this topic has been limited. Therefore, the contribution of this paper is mainly an exploration of the empirical data. The database used is the Spanish General Social Survey (ESGE 2017) prepared by the Sociological Research Center (CIS). The results indicate that personality is the most valued factor, followed by values and physical appearance. The variables with the greatest explanatory power in the estimated multinomial logit model are age, sex, level of education and cohabitation status. Educational homogamy appears among those with higher levels of education, with men more interested in physical appearance and women more interested in values and education. These last two characteristics are also more highly valued among those who are older.
Keywords: Relaciones humanas; Pareja; Intimate relationships; Couple; Preferences; Population 50 and over